Novel, homozygous RAB3GAP1 c.2606 + 1G>A, p.Glu830ValfsTer9 variant and chromosome 3q29 duplication in a Turkish individual with Warburg micro syndrome - ALAVANDA, CEREN; SÖYLEMEZ, MEHMET ALİ; ARMAN, AHMET (My University, 2023)
Warburg micro syndrome (WARBM) is a rare, autosomal recessive, neurodevelopmental disorder characterized by microcephaly, cortical dysplasia, corpus callosum hypoplasia, congenital hypotonia leading to subsequent spastic quadriplegia, severe developmental delay and hypogenitalism. Ophthalmologic findings that may affect any ocular segment including characteristic, small, atonic pupils. WARBM is known to be caused by biallelic, pathogenic variants in at least five genes although additional genetic loci may exist. The RAB3GAP1 c.748 + 1G>A, p.Asp250CysfsTer24 founder variant has been described in families of Turkish ancestry. We report the clinical and molecular findings in three, unrelated, Turkish families with WARBM. A novel c.974-2A>G variant causing WARBM in three siblings of Turkish descent was found. Functional studies of the novel, c.2606 + 1G>A variant in patients\" mRNA revealed skipping of exon 22 which results in a premature stop codon in exon 23. However, the clinical consequences of this variant are blended given that the individual also had a maternally inherited chromosome 3q29 microduplication.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Tıbbi Genetik; Cerrahi Tıp Bilimleri; Patoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Anatomi; Biyokimya; Temel Bilimler; Medicine; Internal Medicine Sciences; Child Health and Diseases; Medical Genetics; Surgery Medicine Sciences; Pathology; Life Sciences; Molecular Biology and Genetics; Health Sciences; Fundamental Medical Sciences; Human Anatomy; Biochemistry; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; PEDİATRİ; PATOLOJİ; ANATOMİ VE MORFOLOJİ; GENETİK VE KALITIM; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; MOLECULAR BIOLOGY & GENETICS; PEDIATRICS; PATHOLOGY; ANATOMY & MORPHOLOGY; GENETICS & HEREDITY; Pediatri, Perinatoloji ve Çocuk Sağlığı; Patoloji ve Adli Tıp; Genetik (klinik); Pediatrics, Perinatology and Child Health; Anatomy; Pathology and Forensic Medicine; Genetics (clinical)